Hypertrichotic Giant Nevus Spilus Tardivus and Neurofibroma of the Tongue in Sporadic von Recklinghausen's Disease - Prabhath Ramakrishnan; Vijay Sylvester; Prathima Sreenivasan; Janisha Vengalath; Smruthi Valambath (Hindawi Limited, 2014)
Solitary neurofibromas are rare, benign tumours of nonodontogenic origin. The presentation of a solitary neurofibroma on the tongue is an uncommon occurrence and we present such a case here which was discovered in concomitance with multiple neurofibromatosis type 1 (von Recklinghausen's disease). Such a rare presentation seen in this case is a diagnostic challenge and often clinched only with the aid of histopathological and immunohistochemical examination. This work also discusses the various differential diagnoses that can be considered in similar cases. The presence of a hypertrichotic "giant" nevus spilus tardivus (Becker's nevus) is also a rare finding in this particular case. We present such a case which will be of interest to the budding dental practitioner. The lesion was excised and the patient followed up without any evidence of malignant transformation.